Application of Evaporative Cooling Ventilation technology to Turbine House of one power plant in Pakistan. (2017) - Tang, Liang; Sun, Defeng; Pan, Jiapeng
Abstract: This paper briefly describes the load characteristics and cooling requirement of Turbine House in one power plant in Sahiwal city of Punjab province in Pakistan, analyses the main equipment and design method of evaporative cooling ventilation system to Turbine House of the power plant, presents several issues which should pay more attention to during design. The evaporative cooling ventilation system performance on site is obviously, with the temperature drop of about 10℃ on our measurement. The research shows that evaporative cooling ventilation technology is practicable and economy for the project and has widely application prospect for similar projects.